2019
DOI: 10.1021/acsami.9b09381
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Photon Spectroscopy Using All Solution-Processed Heterojunctioned Surface-Modified Perovskite Single Crystals

Abstract: Organic−inorganic hybrid perovskites have been intensively studied for their use in optoelectronic devices due to their utilization of lowcost, earth-abundant precursors that are solution-processed at low-temperatures into high-quality devices. Despite this progress, interdevice variability and long-term stability have prevented the widespread commercial adoption of perovskite devices, especially for high-energy photon detectors. Using methylammonium lead iodide perovskite single crystals grown via inversetemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
(131 reference statements)
0
16
0
Order By: Relevance
“…4 ). M–G analysis of I–V data has been used to estimate the carrier mobility (Supplementary Note 4 ) 18 , 42 . The pictures of real devices based on six 2D OIHPs have been shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 ). M–G analysis of I–V data has been used to estimate the carrier mobility (Supplementary Note 4 ) 18 , 42 . The pictures of real devices based on six 2D OIHPs have been shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of defects and the suppression of ion migration are attributed to the passivation of GBs by residual MAAc in the film. Perovskite crystals with low defects and suppressed ion migration are beneficial for long-term stability of films and devices [ 40 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…These 2D perovskites, with general chemical formula (RNH 3 ) 2 ­A n ‑1 ­BX 3 n +1 , are more environmentally stable due to the existence of a protecting organic spacer made of RNH 3 molecules (either aliphatic or aromatic alkyl­ammonium cations), and thus have great potential for the fabrication of long-term stable photovoltaic devices and photodetectors. Pure 2D RP perovskites thin films have been demonstrated in high sensitivity and robust thin-film X-ray detectors . Recently, Joglekar et al showed improved γ-ray detection performance by coating the surface of MAPbI 3 single crystals with a 2D RP perovskite . A 2–3 μm thick 2D RP perovskite film was deposited on the surface of solution-grown MAPbI 3 single crystals through a solution-based alkyl­amine treatment.…”
Section: Perovskite Materials For γ-Ray Detectionmentioning
confidence: 99%